Autoantibodies in neuromuscular transmission disorders - Vincent Angela (Annals of Indian Academy of Neurology, 2008)
It is a great pleasure to be asked to honour the memory of Dr. Baldev Singh by reviewing the field of autoantibodies in myasthenia gravis and other neurotransmission disorders. The neuromuscular junction (NMJ) is the site of a number of different autoimmune and genetic disorders, and it is also the target of many neurotoxins from venomous snakes, spiders, scorpions and other species. The molecular organization of the NMJ is graphically represented in [Figure 1A], where different ion channels, receptors and other proteins are shown. Four of the ion channels or receptors are directly involved in autoimmune diseases. This brief review will not only concentrate on these conditions but also illustrate how their study is helping us to understand the etiology of rare but treatable neurological syndromes of the central nervous system.